Metode Hafalan Al Qur'an Siswa Kelas V Sekolah Dasar Islam Terpadu Ibnu Umar Dan Sekolah Dasar Muhammadiyah Program Khusus Boyolali Tahun 2015 / 2016 - Fatimah, Meti, Dr. Syamsul Hidayat, M.Ag, Dr. Muthoifin, M.Ag (2017)
This research aims to review and to analyze the memorization of the Qur'an graders v integrated Islamic elementary school Ibnu Umar Boyolali and Muhammadiyah elementary school special program Boyolali. Data were collected through observation, interviews, documentation and triangulation, as well as the relevant literature refers to the themes raised. The research's result showed that the method of memorizing the Qur'an which applied in the Integrated Islamic Elementary School Ibn Umar Boyolali with juz'i method, Wahdah, tasmi ', muraja'ah. The memorizing achievement of Quran has reached 50% from the target, 4 juz until graduate from elementary school, there is 65% which has reached 80% ,there is 17% from 23 students. In Muhammadiyah Elementary School Special Program Boyolali used method: Wahdah, talaqqi, Taqrir, muroja'ah.The achievement of memorizing Quran was 80% from the target memorized 30 juz until graduate from primary school has reached 83%. From the achievement of memorizing Quran from both of school it can be concluded that the method of memorizing Quran applied in both of school were effective enough, although need to be developed so the result will be more effective.